Fault location in electrical power systems using intelligent systems techniques. - Souza, J.C.S.
In this work an artificial neural network based methodology is proposed for power systems fault location. Several artificial neural networks are employed, each of them being responsible for detecting faults involving a limited number of components. The proposed methodology is tested using a test system and a real Brazilian system. Indexes based on the Hamming distance are also proposed for feature selection and analysis
Keywords: Brazilian system; Hamming distance; Artificial neural networks; Electrical power systems; Fault location; Feature analysis; Feature selection; Intelligent systems techniques; Pattern recognition; Power system monitoring; Power system protection; Power systems fault location; Test system